1991
DOI: 10.1152/jappl.1991.70.5.1943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogen sulfide exposure on surface properties of lung surfactant

Abstract: Hydrogen sulfide is an irritant and chemical asphyxiant gas that exerts its primary toxic effects on the respiratory and neurological systems. Exposure to hydrogen sulfide above a threshold value of 200-300 ppm is characterized by the sudden onset of hemorrhagic pulmonary edema. The purpose of this study was to determine whether this response is associated with changes in the surface properties of pulmonary surfactant. Bronchoalveolar lavage fluid was retrieved from the lungs of Fischer 344 rats exposed to two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…24 Upon first quasi-static compression, stable minimum surface tensions of about 1 mN/m are achieved with both protein containing surfactants 16,22,26 and synthetic surfactants, provided the film area compression is not limited to 50%. 27 Possible explanations for the relatively higher minimum surface tension measurements in our study include: 1) the phospholipid concentrations in samples from both the control and the EXOSURF group may have been too low (substantially below 50 g/mL of total phospholipid), 2) tracheal aspirate samples may have contained protein inhibitors, [28][29][30][31] or 3) the phospholipid composition in the tracheal aspirates might have been substantially different from that of alveolar surfactant.…”
Section: Discussionmentioning
confidence: 83%
“…24 Upon first quasi-static compression, stable minimum surface tensions of about 1 mN/m are achieved with both protein containing surfactants 16,22,26 and synthetic surfactants, provided the film area compression is not limited to 50%. 27 Possible explanations for the relatively higher minimum surface tension measurements in our study include: 1) the phospholipid concentrations in samples from both the control and the EXOSURF group may have been too low (substantially below 50 g/mL of total phospholipid), 2) tracheal aspirate samples may have contained protein inhibitors, [28][29][30][31] or 3) the phospholipid composition in the tracheal aspirates might have been substantially different from that of alveolar surfactant.…”
Section: Discussionmentioning
confidence: 83%
“…Owens et al [1987] in a study of 69 patients noted this ®nding in a group of 11 subjects who had inhaled potentially toxic substances including ammonia, sulfur dioxide, and pesticides. Parra et al [1991] suggested the development of a mild ®brosis, with some decrease in lung volumes and gas transfer, subsequent to H 2 S inhalation while Green et al [1991] have demonstrated that exposure to H 2 S may adversely affect the properties of pulmonary surfactant.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellu lar toxicity probably depends on the deposi tion of the diacid form in phospholipid struc tures [15].…”
Section: Discussionmentioning
confidence: 99%